Penerapan Algoritma Turbo Boyer Moore Pada Aplikasi Perbandingan Harga Laptop Menggunakan Web - Anggia Utami; A Saehan (AMIK STIEKOM SUMATERA UTARA, 2023)
Laptops have become an integral part of today's society. Whatever work you do, the need for laptops is growing. Technological developments are increasingly rapidly giving rise to various innovations on laptops. When a buyer wants to buy a laptop, many things can be used as criteria. Many laptop brands with various specifications are sold in the market, making it difficult for users to make a choice according to their wishes and budget.String maching uses the Turbo Boyer Moore Algorithm to match the pattern to be searched for, so that you can see the match in pattern selection.It is hoped that through the Turbo Boyer Moore Algorithm it can complete matching in laptop price comparisons so that it can help workers in searching for laptop prices